The Rationale behind Competitive Advantage - Daruka, Peeyush; Sakhalkar, Varuni (2012)
In today’s volatile business environment, a sustainable competitive advantage is what every firm seeks. Much has been said and written on this topic but it has been observed that in their pursuit of growth and diversification, many companies lose out on competitive advantage. The recent economic crisis has but the brakes on growth and market share and the impact has been felt globally across various industries. Reduced customer confidence and spending have made matters worse and companies are being forced to rethink their business model in order to gain an edge over their competitors. The following paper is based on theories of ‘Competitive Advantage’ and how a firm can achieve competitive advantage by leveraging its resources and capabilities. It considers examples of two companies – TUI Travel Plc. and Compass Group Plc.